Assessment of the recreational-tourism resources availability in the Bucovynean Carpathians - Krul, Volodymyr; Krul, Halyna; Palamariuk, Mariia (Kosice, Slovakia, 2016)
The article characterizes preconditions and factors that influence the development of recreation and tourism in the Bukovynian Carpathians. Spatial analysis of distribution of natural, historical, cultural and recreational infrastructure and tourism resources is considered. The general availability of recreational and tourist resources in the region of study on the basis of the rating analysis of absolute and relative performance in terms of village councils is evaluated. Spatial distribution of recreation and tourism centers in the region of study is defined. The ways to the future use of the available recreational-tourism potential for the purposes of tourism and recreation are outlined.
Keywords: recreational and tourist resources; recreation and tourism resources availability; natural and recreational resources; historical and cultural resources; infrastructure resources